Innovation and Transformation Basics, Implementation and Optimization - Kaschny, Martin (Management for Professionals, 2018)
This book discusses a six-step transformation cycle in which the tasks of innovation management - ranked according to their relevance for companies - are placed in a systematic order. Presenting an in-depth discussion on innovation and transformation, the authors delve into strategic themes such as business models and strategic positioning, which are fundamental to the innovation process. It also describes the underlying processes and roles of innovation management, and the required organizational structures. Following process organization and organizational structure, the authors highlight how the appropriate human resource strategy should look and the manner of personnel selection or development to be implemented. The authors also provide tools and systems that are assigned to specific employees working with innovation management; these deal with innovation audit, knowledge management, idea management, financing and budgeting innovations, marketing and property rights. The book also sheds light on how the effectiveness of the innovation process can be monitored using indicator systems. This is a handy resource for managers looking for a structured strategy and how to implement it to achieve optimal innovation management and reap its benefits.